About the solutions of some dynamical games of „peretiagivanije“ and persuit - Murzov, N. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Н. В. Мурзов. О решении некоторых динамических игр перетягивания и преследования N. Murzovas. Kai kurių dinaminių galynėjimosi ir persekiojimo lošimų sprendimas